2022
DOI: 10.1007/s10877-022-00909-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quantitative versus qualitative neuromuscular blockade monitoring on rocuronium consumption in patients undergoing abdominal and gynecological surgery: a retrospective cohort study

Abstract: The level of neuromuscular blockade can be assessed by subjective (qualitative) and objective (quantitative) methods. This study aims to compare the dosage of the neuromuscular blocking agents (NMBA) rocuronium and the need for reversion by sugammadex between those methods. A retrospective, observational analysis was conducted. In the tactile qualitative-neuromuscular monitoring-group (tactile NMM) (n = 244), muscle contractions were assessed tactilely. In the quantitative neuromuscular monitoring-group (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…RNMB, as indicated by the persistence of low TOF ratios, has been associated with various adverse events in the literature, including postoperative respiratory complications. Similar studies [8][9][10][11][12][13][14] in the past emphasize the clinical importance of RNMB detection, as its presence has been linked to factors such as age, type of neuromuscular agents used, and the choice of reversal agents. Esteves et al's study [8] highlights the importance of RNMB detection with a 5.5% incidence rate upon PACU arrival, suggesting that even a modest incidence warrants clinical attention.…”
Section: Incidence Of Postoperative Rnmbmentioning
confidence: 59%
“…RNMB, as indicated by the persistence of low TOF ratios, has been associated with various adverse events in the literature, including postoperative respiratory complications. Similar studies [8][9][10][11][12][13][14] in the past emphasize the clinical importance of RNMB detection, as its presence has been linked to factors such as age, type of neuromuscular agents used, and the choice of reversal agents. Esteves et al's study [8] highlights the importance of RNMB detection with a 5.5% incidence rate upon PACU arrival, suggesting that even a modest incidence warrants clinical attention.…”
Section: Incidence Of Postoperative Rnmbmentioning
confidence: 59%
“…Monitoring of neuromuscular blockade using a simple nerve stimulator is more precise than the simple clinical assessment [ 25 ] which uses pharmacological data; nevertheless, simple monitoring does not allow an estimation of the exact state of neuromuscular paralysis, especially when it is located in intermediate values; visual and tactile estimation are not as accurate, and evaluation remains usually in a lower range compared to quantified instrumental monitoring. Blum et al [ 26 ] recently compared qualitative monitoring (tactile) versus quantitative monitoring (accelerography) in abdominal and gynecological surgery and found quantitative monitoring permitted the use of a lower quantity of muscle relaxants which putatively might decrease the incidence of residual neuromuscular blockade. It should be remembered that simple qualitative monitoring using a nerve stimulator does not yet prevent adverse respiratory effects [ 27 ] or decrease the dose of relaxant given [ 28 ] but remains preferable compared to the total absence of monitoring [ 29 ].…”
Section: Methods Of Neuromuscular Monitoringmentioning
confidence: 99%
“…Batistaki et al reported that 60% of respondents stated that the devices for monitoring the degree of skeletal muscle relaxation should be minimal in the anesthesia workstation [30]. Cyclically implemented recommendations in Great Britain have resulted in a significant increase in the frequency of monitoring the degree of relaxation, from 9 to 31%, and a reduction in the number of respondents who did not routinely use this method, from 62 to 8.9% [13,[31][32][33][34].…”
Section: Professional Perspectivesmentioning
confidence: 99%
“…Recent observational studies have found that the current frequency is up to 32%, but the use of clinical (qualitative) and quantitative observations can reduce this frequency to 18 and 27%, respectively [10][11][12]. Cardiac and thoracic surgery, morbidly obese populations (BMI more than 40 kg/m 2 ), end-stage renal failure, liver dysfunction, and neuromuscular disorders are factors that contribute to ahigher risk of inadequate reversal neuromuscular block, and pediatric and geriatric patients are also at higher risk [13,14].…”
Section: Introductionmentioning
confidence: 99%